2007
DOI: 10.2136/sssaj2006.0254
|View full text |Cite
|
Sign up to set email alerts
|

Field Measurement of Soil Surface Chemical Transport Properties for Comparison of Management Zones

Abstract: Management of chemicals in soil is important, yet the complexity of field soils limits prediction of management effects on transport. To date, few methods have been available for field measurement of chemical transport properties, but a recently developed dripper–time domain reflectometry technique allows rapid collection of data for determining these properties. The objective of this work was to apply this technique for comparison of chemical transport properties for different soil management zones. Experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…For example, Peng et al (2019) and Coppola et al (2016) performed crop water demand predictions, irrigation optimizations and soil salinity controls based on soil EC measurements; Sanches et al (2018) used EC values as a reference to adjust soil pH via lime additions; Yang et al (2019) and Luo et al (2020) measured EC variations of highway roadside soil samples following concrete surface grinding to assess the effects of concrete waste on soil chemical properties and plant growth. In addition, continuous EC measurements over time with specific tracers, e.g., KCl or CaCl 2 , are used to study soil chemical transport properties and provide breakthrough curves for a range of soil types under a variety of managed field conditions, such as compaction or tillage (Gaur et al, 2007;Heitman et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Peng et al (2019) and Coppola et al (2016) performed crop water demand predictions, irrigation optimizations and soil salinity controls based on soil EC measurements; Sanches et al (2018) used EC values as a reference to adjust soil pH via lime additions; Yang et al (2019) and Luo et al (2020) measured EC variations of highway roadside soil samples following concrete surface grinding to assess the effects of concrete waste on soil chemical properties and plant growth. In addition, continuous EC measurements over time with specific tracers, e.g., KCl or CaCl 2 , are used to study soil chemical transport properties and provide breakthrough curves for a range of soil types under a variety of managed field conditions, such as compaction or tillage (Gaur et al, 2007;Heitman et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, these impacts are still poorly understood, and the findings of the few researches that have looked into this topic thus far appear to be contradictory. Compaction is thought to restrict the extent of preferred flow because it interrupts or kills macro pores in soil [16].In sieved and repacked samples, it was discovered that compaction increased preference flow in a sandy loam, whereas preferential flow was recorded in a clay loam at all compaction levels. Dye tracing investigations have shown that any macro holes that remain after the compaction event or those that are subsequently re-generated due to physical (i.e.…”
Section: Introductionmentioning
confidence: 99%